1975
DOI: 10.1098/rspb.1975.0076
|View full text |Cite
|
Sign up to set email alerts
|

Cardenolide storage inDanaus chrysippus(L.) with additional notes onD. plexippus(L.)

Abstract: Danaus chrysippus was reared in the laboratory from stock obtained from Kampala (Uganda), Nairobi (Kenya), Dar-es-Salaam (Tanzania) and Freetown (Sierra Leone) and wild-caught samples from Nigeria, southwest Africa and Tanzania were also analysed. D. plexippus was reared on the same plants for comparison. It was found that the adult D. chrysippus is a poor and inconsistent storer of cardiac glycosides compared with D. plexippus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The question thus arises as to how the polymorphism originated and how it is maintained in an unpalatable species (Rothschild et al, 1975) (Smith, 1980;Smith et al, 1988). D. chrysippus is a savanna butterfly and its present wide distribution in Africa must be a relatively recent phenomenon associated with a decrease in the area covered by forest as a result of a drier climate, accelerated by an unprecedented impoverishment of forest vegetation from human activities, especially in the last few hundred years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question thus arises as to how the polymorphism originated and how it is maintained in an unpalatable species (Rothschild et al, 1975) (Smith, 1980;Smith et al, 1988). D. chrysippus is a savanna butterfly and its present wide distribution in Africa must be a relatively recent phenomenon associated with a decrease in the area covered by forest as a result of a drier climate, accelerated by an unprecedented impoverishment of forest vegetation from human activities, especially in the last few hundred years.…”
Section: Discussionmentioning
confidence: 99%
“…Maps showing the distribution of the forms of D. chrysippus in Africa are given in Owen & Chanter (1968), Owen (1971), Rothschild et al (1975) and Pierre (1973Pierre ( , 1980. The switch between orange and brown ground colour phenotypes (which have not received Latin names) probably has little impact on generalized mimetic resemblance (Gordon, 1984), especially as many of the mimics are similarly variable; Smith (1980) has suggested that the orange-brown polymorphism relates to climatic adaptation, possibly through thermoregulation, influencing activity levels and, in particular, courtship behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the American Danaus spp., the Old World milkweed butterfly, Danaus chrysippus (so-called plain tiger, widely distributed from Africa to tropical Asia) is assumed to be "poisonous" with its conspicuous appearance with a black apex and white subapical spots on the forewing in blight tawny-orange background coloration, likely as a typical model for various mimicry species (Smith 1973 larval stage. However, they are known to be poor and inconsistent sequesterers of CGs (Schneider et al 1975;Rothschild et al 1975;Mebs et al 2005). In order to confirm the toxicity of a local population of D. chrysippus in Okinawa, we examined CG contents in their body tissue.…”
Section: Tiger Danaus Mimicry Ringmentioning
confidence: 99%
“…The polymorphism is unique among the 157 species of the subfamily Danainae (Ackery and Vane-Wright, 1984); it is, moreover, a surprising feature in an aposematic species that is chemically defended (Rothschild et al, 1975;Brower et al, 1975Brower et al, , 1978Brown, 1984; JA Edgar in litt. to DASS) and supports numerous mimics (Smith, 1973a(Smith, , 1976(Smith, , 1979Owen and Smith, 1993;Owen et al, 1994).…”
Section: Introductionmentioning
confidence: 99%